Genes associated to wounding from Aquilaria malaccensis - Wong, Mun Theng; Siah, Chai Har; Qamaruz Zaman, Faridah; Mohamed, Rozi (Faculty of Forestry, Universiti Putra Malaysia, 2013)
Agarwood is an aromatic oleoresin produced by Aquilaria in response to wounding and biological attack but the molecular mechanism is unknown. In this study, several candidate genes in wounding and defense responses were cloned and identified. Deduced amino acid of the cloned sequences exhibited sequence similarities to their respective homologs: transcription factors of the WRKY gene family (AmWRKY) and β-1,3-glucanase (AmGLU). Phenylalanine ammonia-lyase (AmPAL) from previous work was also included. A wounding-stress experiment revealed their expression profiles via qRT-PCR analysis. AmWRKY was induced early after wounding (3 hours), while AmPAL and AmGLU expressions were induced later (16 hours). It is possible that AmWRKY mediates early wounding response while AmPAL mediates response to fungal infection by co-inducing AmGLU.